An investigation of the relationship between lower limb muscle size, strength, and tibia length: A specific analysis of the hamstring and quadriceps muscles - Kadir Keskin; Feride Nur Gogus (ROL Spor Bilimleri Dergisi)
The primary aim of this investigation was to assess the interrelations among the ratios of hamstring-to-quadriceps muscle size and strength, as well as the associations with hamstring and quadriceps muscle size, tibia length, and muscle strength. A total of 47 recreationally active male participants voluntarily took part in the study, with an average age of 21.06±1.52 years, height of 179.47±6.21 cm, body weight of 77.18±10.51 kg, and a body mass index of 23.96±2.97. The knee flexion and extension strength were assessed at a velocity of 60º/s. Additionally, using ultrasonography, the thickness of the total quadriceps muscle, (vastus lateralis, vastus medialis, vastus intermedius, and rectus femoris), and the thickness of the total hamstring muscle (biceps femoris short and long head, semitendinosus, and semimembranosus) were measured at 50% of muscle length. The data were presented as mean and standard deviation, and Pearson product-moment correlation and related samples t-test were utilized for data analysis. The results of the study revealed no significant correlation between the size and strength of the hamstring and quadriceps muscles (r=0.166, p>0.05; r=0.279, p>0.05) and between the H: Q size ratio and H: Q strength ratio (r=0.129, p>0.05). The research findings indicate that the muscle thickness of the knee extensor and flexor muscle groups is not related to the isokinetic force produced in the corresponding muscles, and that muscle thickness is insufficient in determining isokinetic force.